Identificación de variedades de arroz (Oryza sativa L.) fortificadas con características nutracéuticas y nutricionales - Rojas Reyes, Dannis Wilmer (2024)
One of the strategies to repower crops to address nutritional and other deficiencies, in order to improve the agronomic qualities and increase the nutritional qualities of the products of the harvest, and for this purpose rice is one of the main ones on the list because it is one of the most consumed worldwide. In this work, a compilation of information is made in order to identify fortified rice varieties with nutraceutical and nutritional characteristics and to specify their uses and properties. It was recorded that Oryza sativa L., is a primary food in the diet of human beings, providing approximately 23% of the caloric needs worldwide. Currently there are more than 40,000 types of rice around the world, each with its special characteristics for which they are chosen for each objective, as a source of energy, strengthening of the immune system and of course nutrition; Plus, they're low in fat, high in sodium with plenty of carbohydrates and protein. About ten types of rice are produced in Ecuador, including long, white, brown, black, aromatic and red rice. In Ecuador, rice has a variety of uses in local cuisine and culture, as a staple food. Rice is an important food in the Ecuadorian diet and is consumed in a wide variety of dishes. It is a fundamental part of traditional dishes. Accompaniment: Rice is often served as an accompaniment to main dishes; Desserts: In some regions of Ecuador, sweet desserts are prepared based on rice; Beverages: Rice is also used in the preparation of traditional beverages. Culture: Rice has an important cultural significance in Ecuador, being part of traditional celebrations and festivities.